Implementation of the Direct Cash Assistance Program for Village Funds - Yanti, Hernis Yunita Norma; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2024)
General Background: The COVID-19 pandemic has necessitated government interventions in Indonesia to support vulnerable populations. Specific Background: One such intervention is the Direct Cash Assistance Program from Village Funds (BLT-DD), aimed at alleviating economic burdens. Knowledge Gap: Despite its implementation, challenges in recipient targeting and data accuracy remain. Aims: This study analyzes the BLT-DD program's implementation in Sidodadi Village, focusing on success factors and barriers. Results: Qualitative methods reveal that while communication among stakeholders is strong, issues like multiple assistance to some beneficiaries lead to inequalities. Novelty: The study utilizes Van Meter and Van Horn’s implementation theory to provide insights into the program's challenges. Implications: Findings highlight the need for improved data management and stakeholder engagement to enhance equitable distribution of assistance and foster economic recovery in rural areas. Highlights: Targeting Issues: Some beneficiaries received multiple forms of assistance, leading to inequities. Communication Strength: Effective coordination among stakeholders facilitated the program's implementation. Data Management Needs: Improved data validity is crucial for enhancing program effectiveness and fairness. Keywords: BLT-DD, COVID-19, Village Funds, Economic Assistance, Implementation